P2X1 receptor-mediated pressor responses in the anesthetized mouse - Lu Li; Yi Wu; Mo Deng; Guangyi Wu; Leiming Ren (Elsevier, 2012)
P2X1 receptors and adrenoceptors are mainly responsible for vasoconstriction in a variety of blood vessels. However, previous studies have shown that α,β-methylene adenosine 5'-triphosphate (α,β-MeATP), a stable analogue of ATP, can induce both pressor and depressor responses in laboratory animals. In this study, the effects of increasing intravenous doses of α,β-MeATP and noradrenaline (NA) (0-30 nmol/kg) administered at 20 min intervals on systolic (SBP), diastolic (DBP) and mean (MBP) blood pressure in groups of anesthetized mice (n=6) were compared. Both α,β-MeATP and NA caused transient, dose-dependent increases in SBP, DBP and MBP but the effect of α,β-MeATP was more rapid and significantly larger at doses of 10 and 30 nmol/kg (P<0.01). At the dose of 30 nmol/kg, α,β-MeATP increased SBP, DBP and MBP by 65.8±7.0, 65.7±5.0 and 65.7±5.5 mmHg, respectively, compared to increases of 36.8±4.6, 33.3±4.9 and 34.5±4.7 mmHg, respectively, produced by NA. These results indicate P2X1 receptors play an important role in BP regulation although purinergic vasoconstriction alone may not explain the more potent pressor response to α,β-MeATP in the anesthetized mouse.